A novel model and sensitive analysis for productivity estimate of nitrogen assisted cyclic steam stimulation in a vertical well. (November 2018) - Wu, Zhengbin; Liu, Huiqing; Zhang, Zequan; Wang, Xue
Highlights: A novel heated radius calculation model is established. A novel productivity prediction model is derived for the NCSS in a vertical well. The productivity prediction model works more accurately. Abstract: Nitrogen-assisted cyclic steam stimulation (NCSS, i.e. huff and puff) is an important alternative to recover heavy oil reservoirs. In order to forecast the production performance accurately and rapidly, a novel model is developed for heated radius calculation and production prediction of NCSS wells. The underlying assumption in this paper is different from the Marx-Langenheim isothermal model, the heated area is assumed to be non-isothermal and the temperature decreases exponentially. A new heated radius calculation equation is then established and solved by the Newton iteration method. Afterwards, an analytical model for production prediction is derived with pseudo-steady state percolation method by considering the variation of temperature, pressure, relative permeability, etc. during the different periods of the huff-n-puff process. After verification by numerical simulation runs, a sensitivity analysis is performed with the consideration of multiple factors, such as injection rate, injection temperature, fluid component and threshold pressure gradient (TPG). The results indicate that the increase of injection rate, injection temperature and nitrogen-steam ratio, or the decrease of TPG will lead to an increase in oil production. This paper provided a reference for heated radius evaluation and productivity estimation in NCSS processes for heavy oil.